Global warming and the climate crisis science, spirit, and solutions - Johansen, Bruce E. (Springer, 2023)
This textbook introduces readers to basic scientific principles of climate change. Based on extensive empirical evidence, it explains weather events that indicate climate changes evolution and presents important topics connected to climate change, such as political controversies, climate policy, as well as Native American perspectives. Finally, it presents attempted solutions, including policy recommendations and technological proposals for necessary changes in our world. Providing a well-written and easy-to-follow overview of knowledge of science-based geophysical facts, including thermodynamics, the book puts a strong emphasis on why expeditious action on global warming is urgent. The book also explains why smart greenhouse-gas reduction strategies will ignite economic growth, generate new domestic jobs, protect public health, and strengthen energy security. Not assuming a scientific background on the part of the reader, Global Warming and the Climate Crisis: Science, Spirit, and Solutions offers an ideal supplemental reading in many types of courses in Earth sciences, climate policy, climate change sciences, as well as politics of climate change, from high school through undergraduate. General readers also will benefit from its treatment of this very important and timely issue.-- Back cover.